HEMORHEOLOGY INDEX CHANGES IN A RAT ACUTE BLOOD STASIS MODEL: A SYSTEMATIC REVIEW AND META-ANALYSIS - Zhang, Jun-Xiu; Feng, Yu; Zhang, Yin; Liu, Yi; Li, Shao-Dan; Yang, Ming-Hui (African Journal of Traditional, Complementary and Alternative Medicines, 2017)
Background: Blood stasis has received increasing attention in research related to traditional Chinese medicine (TCM) and integrative Chinese and Western medicine. More than 90% of research studies use hemorheology indexes to evaluate the establishment of animal blood stasis models rather than pathological methods, as hemorheology index evaluations of blood stasis were short of the consolidated standard. The aim of this study was to evaluate the accuracy of hemorheology indexes in rat models of acute blood stasis (ABS) based on studies in which the ABS model had been confirmed by pathological methods. Materials and Methods: We searched the Chinese National Knowledge Infrastructure database (CNKI), Chinese Medical Journal Database (CMJD), Chinese Biology Medicine disc (CBM), Wanfang database, and PubMed for studies of rat blood stasis models; the search identified 18 studies of rat ABS models induced by subcutaneous injection of epinephrine combined with an ice bath. Each included study received a modified Collaborative Approach to Meta-Analysis and Review of Animal Data from Experimental Studies (CAMARADES) score list and methodological quality assessment, then data related to whole blood viscosity, plasma viscosity, platelet aggregation rate, erythrocyte aggregation index, and fibrinogen concentration were extracted. Extracted data were analyzed using Revman 5.3; heterogeneity was tested using Egger’s test. Results: A total of 343 studies of rat blood stasis were reviewed. Eighteen studies were included in this meta-analysis; the mean CAMARADES score was 3.5. The rat ABS model revealed a significant increase in whole blood viscosity (medium shear rate), whole blood viscosity (high shear rate), plasma viscosity, platelet aggregation rate, erythrocyte aggregation index, and fibrinogen concentration compared to controls, with weighted mean differences (WMD) of 2.42 mPa/s (95% confidence interval (CI) = 1.73 - 3.10); 1.76 mPa/s (95% CI = 1.28 - 2.24); 0.39 mPa/s (95% CI = 0.24 - 0.55); 13.66% (95% CI = 9.78 - 17.55); 0.84 (95% CI = 0.53 - 1.16); and 1.22 g/L (95% CI = 0.76 - 1.67), respectively. Subgroup analysis showed that whole blood viscosity, plasma viscosity, and the platelet aggregation rate test methods were more sensitive when measured at 0-24 h than at 24-72 h after induction of blood stasis. Conclusions: Rat blood stasis studies have incomplete experimental design and quality controls, and thus need an integrated improvement. Meta-analysis of included studies indicated that the unified hemorheology index of whole blood viscosity (medium and high shear rate), platelet aggregation rate, erythrocyte aggregation rate, and fibrinogen concentration might be used for assessment of rat ABS models independent of pathology methods.